A juventude está on: modos de afrontamento ao discurso de ódio no território escolar - Holanda, Rochelly Rodrigues (2025)
The connection between dealing with sensitive situations experienced on the internet and the increase in cases of hate speech, prejudice and violence in the school context has demanded greater attention in the public debate and has become the object of our reflections. In view of the above, the present study was constituted by the following guiding question: How is hate speech configured in the experiences lived by high school students from a campus of the Federal Institute of Education, Science and Technology in the interior of northeastern Brazil? The main objective is: To map how the experiences of hate speech lived by high school students from a campus of the Federal Institute of Education, Science and Technology in the interior of northeastern Brazil are configured. As developments of this, we list the following specific objectives: 1) To debate the concept of ‘hate speech’ as a discursive policy and its intersections in school territories; 2) To promote participatory methodologies oriented towards the implication of the methodological field of Intervention Research that foster dialogue and Research WITH young people in school about the experience of hate speech. 3) To assess how the context of the Covid-19 pandemic has impacted the blurring of boundaries between online and offline and the resurgence of hate speech in educational territories. 4) To analyze the engendering of hate speech in discursive practices and its possible forms of confrontation in everyday school life. Methodologically, this is a qualitative study, through an Intervention Research (IP) design, anchored in the political power of Research WITH youth and WITH public schools and in the management of the cartographic ethos. The cartographic artifacts and participatory devices operationalized in the work were: 1) Participant observation; 2) Creation of Travessias: Research and Intervention Group on Subjectivities, Societies and Education; 3) Online questionnaires; 4) Extension Course; 5) Field diaries, plural diaries: Youth and School in the Fight against Hate Speech; 6) School restitution: the construction of the resistance mural. At the end of this research, 27 young people aged 15 to 19 participated. The analyses carried out in this work are guided by post-structuralism in a Foucaultian analysis of discourse. As a result, we evidenced the blurring of boundaries between online and offline regarding the debate on Hate Speech in everyday school life, highlighting as main analyzers: a) Hate speech on digital platforms: New contours to the experience in the post-pandemic period; b) Hate narratives and the construction of a common ground in the group with young students; c) Youth perspectives on hate narratives in public schools; d) Neoliberalism and Education: How competitiveness amplifies hate speech; e) Confrontations to hate speech from the perspective of young people in the school environment. The research presented offers contributions to the field of studies on education, youth and hate speech in the school context. The emphasis is on the construction of confrontation strategies, which emerge as an important resistance device, highlighting the possibility of mobilizing youth to question and subvert oppressive practices, creating spaces for collective speech and action in the school environment.